A combination of Electron Spin Resonance spectroscopy/atom transfer radical polymerization (ESR/ATRP) techniques for fundamental investigation of radical polymerizations of (meth)acrylates. (18th August 2015) - Kajiwara, Atsushi
Abstract: This paper results from combining Electron Spin Resonance (ESR) spectroscopy and atom transfer radical polymerization (ATRP) to study the basic chemistry of radical polymerizations. This combination of analytical and controlled preparation techniques can provide information on chain length of propagating radicals and chain transfer reactions to polymers which has been previously difficult or impossible to study by direct detection of radicals in radical polymerizations by ESR. Two results are obtained by the ESR/ATRP combination technique. The first provides an estimation of the effect of chain length on the structure of methacrylate propagating radicals, especially in the initial stage of radical polymerizations. Model radical precursors of dimeric, trimeric, tetrameric, and pentameric structures of t BMA and MMA were prepared by ATRP. The corresponding model radicals were generated from these precursors and were observed by ESR at various temperatures. The ESR spectra provided direct information on chain length dependent changes of the averaged structures at the chain ends of the model propagating radicals, indicating that distortion in dihedral angles between chain end pπ-orbital and Cβ -H bonds increased with increasing chain length. The second result provides information on the radical migration reactions during the polymerization of acrylates. Radical precursors of ethyl-, n- butyl-, and dodecyl acrylates with various chain lengths (DP = 10, 25, 60, etc.) were prepared by ATRP. Model propagating radicals were generated from these precursors and were observed by ESR at various temperatures. These radicals showed chain length dependent spectroscopic change due to radical migration reactions from model propagating to mid-chain radicals with increasing temperature. Longer chained radicals with the same ester side groups showed easier formation of mid-chain radicals. An examination of side group dependency indicated that, longer alkyl side groups showed easier radical migration reactions. The development of ATRP enabled us to resolve these problems associated with side reactions in radical polymerizations. Graphical abstract: Highlights: This paper results from combining Electron Spin Resonance (ESR) spectroscopy and atom transfer radical polymerization (ATRP) to study the basic chemistry of radical polymerizations. This combination of analytical and controlled preparation techniques can provide information on chain length of propagating radicals of methacrylates and chain transfer reactions during acrylate radical polymerizations which has been previously difficult or impossible to study by direct detection of radicals in radical polymerizations by ESR. The development of ATRP enabled us to resolve the problems associated with both chain lengths of propagating radicals and side reactions in radical polymerizations.